2020
DOI: 10.2147/cmar.s237146
|View full text |Cite
|
Sign up to set email alerts
|

<p>Astragalus Polysaccharide Promotes Adriamycin-Induced Apoptosis in Gastric Cancer Cells</p>

Abstract: Astragalus polysaccharide (APS), a common Chinese herbal compound extracted from Astragalus membranaceus, has been proposed to increase the tumour response of and stabilize chemotherapy drugs while reducing their toxicity. Here, we examined the effects of APS on apoptosis in gastric cancer (GC) cells in the presence or absence of adriamycin (0.1 µg/mL). Methods: GC cells cultured in the presence or absence of adriamycin (0.1 µg/mL) were administered APS (50-200 µg/mL) for 24-72 h and subjected to an MTT assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Most of studies have clari ed that APS inhibit tumor growth through immunopotentiation activity and generally be considered as a powerful adjunctive strategy in combination with chemotherapy for various tumors [15,16]. There are also parts of studies suggest the direct anti-tumor activity of APS, such as the inhibition of cell proliferation, the induction of cell apoptosis and cell cycle arrest [17,18]. In the present study, for the rst time, we employed bioinformatics approach to speci cally target the common hub genes involved in the in vitro anti-tumor biological processes, and further underwent experimental veri cation.…”
Section: Discussionmentioning
confidence: 99%
“…Most of studies have clari ed that APS inhibit tumor growth through immunopotentiation activity and generally be considered as a powerful adjunctive strategy in combination with chemotherapy for various tumors [15,16]. There are also parts of studies suggest the direct anti-tumor activity of APS, such as the inhibition of cell proliferation, the induction of cell apoptosis and cell cycle arrest [17,18]. In the present study, for the rst time, we employed bioinformatics approach to speci cally target the common hub genes involved in the in vitro anti-tumor biological processes, and further underwent experimental veri cation.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, the administration of Astragalus extract decreased the viability and induced the apoptosis of gastric cancer cell line via the AMPK pathway (Song et al 2020). Zhang et al (2018a) investigated that the ovarian cancer cell invasion and migration were inhibited through a decrease in the phosphorylation of ERK and the expression of MMP-2/9 (Zhang et al 2018a).…”
Section: Health-promoting Activities Of Astragalus (Astragalus Membranaceus) Based On In Vitro Studiesmentioning
confidence: 99%
“…APS could also act synergistically or additively with standard chemotherapeutic agents, therefore reducing the dosing of standard chemotherapy and minimizing toxic side effects. In a recent study, APS has been shown to promote apoptotic effects of Adriamycin on gastric carcinoma cells when used in combination with Adriamycin [ 72 ]. The results of this study indicate that the mechanism for the anticancer activity was mediated through the AMPK pathway and APS can synergistically act with Adriamycin to enhance its anticancer activity [ 72 ].…”
Section: The Potential Use Of Astragalus and Shiitake As Adjuvants In Chemotherapymentioning
confidence: 99%
“…In a recent study, APS has been shown to promote apoptotic effects of Adriamycin on gastric carcinoma cells when used in combination with Adriamycin [ 72 ]. The results of this study indicate that the mechanism for the anticancer activity was mediated through the AMPK pathway and APS can synergistically act with Adriamycin to enhance its anticancer activity [ 72 ]. In another study, Apatinib (a tyrosine kinase inhibitor used in many cancer targeted therapies), when used in combination with APS, showed enhanced anticancer effect on pancreatic cancer cells by reducing cell invasion and migration significantly compared to Apatinib monotherapy [ 73 ].…”
Section: The Potential Use Of Astragalus and Shiitake As Adjuvants In Chemotherapymentioning
confidence: 99%